Nature’s lubrication solutions - Jacob Klein (Friction)
We briefly review the organizing principles that nature has selected to reduce friction between sliding tissues in the body to maintain their well-being. This is of especial relevance where large stresses are involved, such as in the major joints (hips and knees), where lubrication breakdown, wear, and degradation of articular cartilage are associated with osteoarthritis, the most common and debilitating joint disease affecting hundreds of millions worldwide. In particular, in light of recent experiments, we revisit the fundamental issue of the mechanisms responsible for lubrication of articular cartilage in synovial joints. We conclude from these direct studies that lubrication by lipid-based boundary layers rather than interstitial fluid pressurization plays a major role in cartilage lubrication. We also review the development of new material properties for synthetic hydrogels inspired by this lubrication mechanism of cartilage, a complex bio-hydrogel, which hold strong potential for novel applications. Finally, we consider briefly the intriguing question of why there is a large proliferation of different lipids (well over a hundred) in the cartilage and in the synovial fluid surrounding it when experiments show that single-component lipid layers can provide excellent lubrication: Is this simply natural redundancy, or does it carry benefits for lubrication?